The Existence of Employee Cooperatives as Organisational Support: A Survey of Members and the Role of Cooperative Managers - Sarsalos Sivakkar; Jaka Purnama (Penerbit Jurnal Indonesia, 2024)
Employee cooperatives are part of a group or organization that contains people who agree and agree in supporting the common economy, besides that employee cooperatives also function as supporting factors for an institution, where the chairman and members are people in the institution itself, employee cooperatives are a forum for help in supporting common welfare, the development of technology is declining as well as the existence of employee cooperatives themselves In an institution, for that the author is very interested in examining the extent of employee cooperative support for institutions or organizations, the author uses descriptive qualitative methods where this method is pure research conducted and directed to understand organizational problems in depth and for the development of administrative and management science, which is based on reality and elements of positivism regarding the existence of cooperatives.